Use of Transnational Law as a Tool of Political Pressure and Coercion - Tan, Richie Lay; Sunadynatha, Rama Adi Saputra; Wonohadidjojo, Christopher Howard (CV. Rayyan Dwi Bharata, 2023)
Transnational law is a law that regulates and limits the actions of states. In its application, many of the methods permitted by transnational law are used by a stronger state to coerce the attitudes and actions of a weaker state. Despite its uncertain effectiveness, this phenomenon is a common occurrence and often ends in violations of the human rights of the people of the affected countries.